ANALISIS PETROFISIKA UNTUK MENENTUKAN OIL-WATER CONTACT PADA FORMASI TALANGAKAR, LAPANGAN “FBT”, CEKUNGAN SUMATRA SELATAN - Febrina Bunga Tarigan; Ordas Dewanto; Karyanto Karyanto; Rahmat Catur Wibowo; Andika Widyasari (Jurnal Geofisika Eksplorasi, 2019)
In conducting petrophysics analysis, there are many methods on each property. Therefore, it is necessary to determine the exact method on each petrophysical property suitable for application in the field of research in order to avoid irregularities at the time of interpretation. The petrophysical property consists of volume shale, porosity, water saturation, etc. This research used six well data named FBT01, FBT02, FBT03, FBT04, FBT05, and FBT06 and also assisted with core data contained in FBT03. Core data used as a reference in petrophysical analysis because it was considered to have represented or closed to the actual reservoir conditions in the field. The area in this research was in Talangakar Formation, "FBT" Field, South Sumatra Basin. The most suited volume shale method for “FBT” field condition was gamma ray-neutron-density method by seeing its photo core and lithology. As for the effective porosity, the most suited method for the field was neutron-density-sonic method by its core. Oil-water contact was useful to determine the hydrocarbon reserves. Oil-water contact was obtained at a depth of 2277.5 feet on FBT01, 2226.5 feet on FBT02, 2312.5 feet on FBT03, 2331 feet on FBT04, 2296 feet on FBT05, and 2283.5 feet on FBT06. The oil-water contact depth differences at Talangakar formation in FBT field caused by structure in subsurface.